Emodin attenuates Alzheimer's disease by activating the protein kinase C signaling pathway - Du, Changwang; Shi, Luoning; Wang, Mei; Mao, Ping; Wang, Jia; Wei, Yanqiang; Hou, Juanru; Wang, Maode (Cellular and Molecular Biology, 2019)
To investigate the effects of emodin on learning and memory and protein kinase C (PKC) signaling pathway in Alzheimer's disease (AD) model mice. 60 APP/PS1 double transgenic AD mice were selected as model mice at the age of 7-8 months, 36 healthy male C57BL/6 mice served as the control group. Morris water maze method and passive avoidance experiment were used to evaluate the memory ability of mice. The thiazole blue (MTT) method and the lactate dehydrogenase (LDH) cytotoxicity test kit were used to evaluate the effect of emodin on the cell viability of hippocampal neurons in HT22 mice treated with Î²-amyloid peptide 1-42 (AÎ²1-42). The effect of emodin on PKC levels was explored using the modified Takai method and Western blotting. Behavioral test results showed that the escape latency of the mice in the model group was longer than that in the control group (P<0.05), and the escape latency was significantly shortened given a emodin prognosis. The MTT and LDH test results showed that emodin to AÎ²- overexpression induced the protective effect of hippocampus cells in HT22 mice. Western blot analysis showed that the phosphorylation level of PKC in mice increased significantly after emodin administration. Emodin can attenuate oxidative stress and inflammatory response in Alzheimer's model mice by activating PKC pathway, thereby improving cognitive function.